UV-B and Biosphere 1997
DOI: 10.1007/978-94-011-5718-6_25
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric ozone reduction and ecosystem processes: enhanced UV-B radiation affects chemical quality and decomposition of leaves of the dune grassland species Calamagrostis epigeios

Abstract: This study reports changes in the plant's chemical composition and the decomposition of this plant material under enhanced solar UV-B radiation. Calamagrostis epigeios, a dominant grass species in the dune grassland in The Netherlands, was grown outdoor on an experimental field under ambient and enhanced solar UV-B (5 and 7.5 kJ m-2 day-l UV-BBE, respectively), corresponding to about 15% stratospheric ozone depletion. After one growing season aerial plant parts were harvested. The decomposition of this harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
92
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 35 publications
(32 reference statements)
8
92
3
Order By: Relevance
“…Our study did find that UV photodegradation increased the breakdown of the 363 hemicellulose fraction by 26% (Fig. 3b), which is consistent with previous studies 364 (Rozema et al 1997;Brandt et al 2010). We also found that UV photodegradation 365 increased the loss of cellulose by 11% (Fig.…”
supporting
confidence: 92%
“…Our study did find that UV photodegradation increased the breakdown of the 363 hemicellulose fraction by 26% (Fig. 3b), which is consistent with previous studies 364 (Rozema et al 1997;Brandt et al 2010). We also found that UV photodegradation 365 increased the loss of cellulose by 11% (Fig.…”
supporting
confidence: 92%
“…In general, lignin has a high resistance to microbial enzymes, but it is sensitive to different wavelengths of ultraviolet radiation (Rozema et al 1997). It seemed possible that lignin decomposed into watersoluble species without relevant gas emission (Gould 1982;Lanzalunga and Bietti 2000;Henry et al 2008).…”
Section: Straw Chemical Compositionmentioning
confidence: 99%
“…It is thought that lignin-like compounds in litter should be the most susceptible to photodegradation, due to the presence of aromatic rings that can absorb UV wavelengths. There has been some evidence for this mechanism in the lab (Brandt et al 2009, Austin and BallareÂŽ2010, Lee et al 2012 and in the field (Gehrke et al 1995, Rozema et al 1997, Day et al 2007, Gallo et al 2009), but recent field studies have shown mixed (Brandt et al 2007(Brandt et al , 2010 or nonexistent (Lin and King 2014) effects of UV on the lignin fraction in litter.…”
Section: Introductionmentioning
confidence: 97%